1995
DOI: 10.1016/s0022-5223(05)80007-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased accuracy and precision of heparin and protamine dosing reduces blood loss and transfusion in patients undergoing primary cardiac operations

Abstract: Individual aspects of heparin or protamine dosing have been better controlled than previously as useful tests have become available. Although many variables including drug potency, drug source, and individual patient response have been separately identified, there has not been an attempt to integrate them into a single management strategy. This study was undertaken to learn whether more precise control of drug variables and patient response would affect blood loss and transfusion requirements. Adult patients h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
67
1
6

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(75 citation statements)
references
References 27 publications
1
67
1
6
Order By: Relevance
“…7 Earlier studies reported an incidence of heparin rebound varying from 4% to 54%. [8][9][10][11][12][13] However, a more recent study has suggested that residual circulating heparin is present in virtually all patients following cardiac surgery. 14 We have shown, in a recent survey, that most cardiac surgical centers in Canada do not use point of care tests in the management of postoperative cardiac surgical patients.…”
mentioning
confidence: 99%
“…7 Earlier studies reported an incidence of heparin rebound varying from 4% to 54%. [8][9][10][11][12][13] However, a more recent study has suggested that residual circulating heparin is present in virtually all patients following cardiac surgery. 14 We have shown, in a recent survey, that most cardiac surgical centers in Canada do not use point of care tests in the management of postoperative cardiac surgical patients.…”
mentioning
confidence: 99%
“…12,13 Using the RxDx system, we measured the heparin sensitivity and constructed individualised dose response curves for each patient. Heparin sensitivity was not different among the four patient groups, and the calculated dose of heparin using the titration was not different among the four groups.…”
Section: Discussionmentioning
confidence: 99%
“…The reversal of heparin with protamine may affect bleeding and tranfusion as protamine itself is an anticoagulant. Despite the lack of definitive data, titration and empric low-dose regimen of protamine therapy may both lower the dosage of protamine and reduce bleeding and tranfusion (Jobes et al, 1995;Shore-Lesserson et al, 1998). Leukofiltration, ultrafiltration or infusion of shed mediastinal blood are other interventions that are addressed in clinical trials (Augoustides et al,2009).…”
Section: Postoperative Bleeding and Transfusionmentioning
confidence: 99%